Soroprevalência da infecção pelo vírus da hepatite A em catadores de materiais recicláveis em Goiânia, Goiás - Soares, Helen de Oliveira (2013)
Hepatitis A virus (HAV) is mainly transmitted by the oral-fecal route. HAV infection prevalence is associated with socio-economic and hygienic conditions. In Brazil, hepatitis A is considered an endemic infection and some studies have shown a shift from high to intermediate endemicity pattern. Almost recyclable waste collectors have a lifestyle that is characterized by precarious social, cultural and environmental factors. The epidemiological status of HAV infections of these workers remains unknown. So, this study aimed to investigate the hepatitis A virus infection profile in recyclable waste collectors in Goiânia, Goiás. A cross-sectional survey was carried out with 431 individuals who were recruited in all 15 recycling cooperatives in Goiânia, Goiás. All individuals were interviewed and their serum samples were tested for anti-HAV total marker by enzyme-linked immunosorbent assay (ELISA). Total anti-HAV positive samples were tested for IgM anti-HAV marker by ELISA. Almost all population (429/431) was positive for total anti-HAV antibodies. By contrast, none were IgM anti-HAV positive. The seroprevalence of HAV infection among recyclable waste collectors in Goiânia-Goiás was 99,5% (IC 95%: 98,1-99,9). Unfavorable socio-economic, sanitary and house conditions (low education and family income, high number of people at home and lack of treated/filtered water), as well as risk practices (contact with contaminated waste, irregular use of gloves and eating from the garbage) were reported by a considerable percentage of participants. These findings highlight the need of actions of health promotion and diseases prevention to the population of recyclable waste collectors in Goiânia, Goiás.